Epidemiology of Cutaneous Leishmaniasis and Its Diagnosis Using Polymerase Chain Reaction Technique in Salah Al-Din Governorate. - Hassan , Ahmed Abdulraheem; Shakir , Ohood Mozahim (Universitas Muhammadiyah Sidoarjo, 2025)
The study, conducted from October 2022 to March 2023, aimed to detect cutaneous leishmaniasis in 169 samples from visitors to Samarra General Hospital and dermatology outpatient clinics. Samples were confirmed via direct smear and PCR techniques. The study examined the spread of the parasite by various factors, revealing a higher infection rate in rural areas (64.5%) compared to urban areas (35.5%). The highest infection rate was observed in children aged 1-10 years (21.89%), followed by those aged 21-30 years (17.7%), while the lowest infection rate was in individuals aged 61-70 years (4.73%). Wet ulcers were more common (75.1%) than dry ulcers (24.9%). The infection rate was highest in January (27.22%), followed by February (21.89%), with March showing the lowest rate (10.65%). Facial infections were most common (42.6%), followed by lower extremities (40.23%), and the trunk had the lowest incidence (0.59%). Molecular analysis using PCR revealed that L. major was the predominant type (68.64%), with L. tropica accounting for 31.36%. Males showed a higher infection rate for both types, with L. major affecting 44.38% of males compared to 24.26% of females, and L. tropica infecting 21.3% of males versus 10.06% of females. Highlights: Study on cutaneous leishmaniasis in 169 samples, confirmed by smear and PCR. Higher infection in rural areas, children, wet ulcers, and January-March period. L.major prevalent (68.64%), higher male infection rates in both parasite types. Keywords: leishmaniasis, pcr, diagnosis ,leishmania tropica, lishmania major